LANGUAGE GAME IN ADVERTISING DISCOURSE: BASED ON ENGLISH AND UZBEK LANGUAGE ADVERTISING (Journal of Universal Science Research, 2025)
Language plays a crucial role in advertising by shaping consumer perception and engagement. One of the most effective linguistic strategies employed in advertising discourse is the "language game," which involves wordplay, puns, metaphors, and other rhetorical devices to capture audience attention. This paper explores the use of the language game in English and Uzbek advertisements, highlighting similarities and differences. The study integrates insights from linguists and marketing experts to analyze how language manipulation enhances the persuasiveness of advertisements.